EXTENSION OF THE PRESIDENTIAL TERM AND EFFORTS TO STRENGTHEN THE POST-COVID 19 PARLIAMENTARY SYSTEM - MH, Erfandi (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2022)
Extention of the term of office of the President and/or Vice President is considered unconstitutional. Because it is contrary to the original intent and spirit of the 1945 Constitution. However, legal political efforts can be made constitutionally to extend the term of office of the President and/or Vice President through legal changes to the constitution. In addition, it is also necessary to strengthen the parliament in order to create a balance of power between the legislature and the executive in order to achieve democratization in the future state administration